OPTIMISM OF W.SHEKSPEARE`S TRAGEDIES - Karimova Dilafruz Javlonbek Qizi; Jumaeva Nasiba Komil qizi (Лучшие интеллектуальные исследования, 2024)
In the past, Europe, America, Africa, and Australia had their own distinct religions before adopting Asian religions. However, these native religions either disappeared or lost influence due to the dominance of Asian belief systems. Understanding this historical context is crucial when considering the interactions between Western artists and the East, as well as the impact of Oriental science and literature. The West approached the East with particular needs and expectations until it strengthened its philosophical, theoretical, and scientific foundations. When examining comparative literature, the distinction between East and West becomes less significant. Consequently, the role of the East is noteworthy in Shakespeare's work, as it exhibits numerous Oriental parallels.